(untitled) (International Journal of Food and Nutritional Sciences, 2022)
COVID-19 leads to isolation because people have to remain at home to prevent infection, but this is likely to have a detrimental effect on the physical and mental health of individuals.From the perspective of prevention, a healthy lifestyle is crucial. Lifestyle has been defined diversely and comprehensively in research and is still being studied. Lifestyle can be classified according to people’s life patterns, and can be defined as a complex concept that involves a person’s consciousness of life, values, and character. Drinking, smoking, exercise, nutrition, and stress are also elements of lifestyle according to the WHO’s definition of the term. Previous studies have highlighted the importance of healthy lifestyles as they are crucial in maintaining and improving physical and mental health and improving the quality of life.